EPISTEMOLOGI HERMENEUTIKA DALAM WACANA TAFSIR - Hasiolan (EL-ADABI : Jurnal Studi Islam, 2023)
Hermeneutics as a new approach in the world of interpretation has received various responses from Muslims. However, hemeneutics is still considered not well-established enough to be used as an approach to the interpretation of the Koran because it was not originally intended for the Koran. In addition, the Koran cannot be equated with other textswhich are the result of human hands while the Koran comes from Allah SWT, according to Islamic beliefs. This paper will review the epistemology of hermeneutics by looking at the views of its figures such as Friedrich Schleiermacher, Wilhelm Dilthey, Martin Heiddegger, Paul Ricoeur, Hans-Georg Gadamer. The research method used is library research. It was found that the use of hermeneutics as an approach in interpreting the Qur'an, was responded in three forms, namely groups that support, groups that reject and groups that do not fully support nor completely reject.